Influence of blockchain and smart contracts on partners’ trust, visibility, competitiveness, and environmental performance in manufacturing supply chains - Chen, Ping-Kuo; He, Qiu-Rui; Chu, Shiping (Journal of Business Economics and Management, 2022)
This study investigates the influence of blockchain and smart contracts on partners’ trust, increasing visibility, competitiveness, and environmental performance when implemented in manufacturing supply chains. Partial least squares (PLS) was the main method used to test and verify the research model and hypotheses. According to the test results, blockchain and smart contracts positively influence partners’ trust. Increasing trust produces a positive effect on increasing visibility, further promoting competitiveness and environmental performance. However, the vulnerability of smart contracts still causes information security concerns. If smart contracts are adopted for an extended time, partners will worry about problems of information vulnerability stemming from the smart contract, further reducing trust and affecting visibility. Regarding academic implications, this study not only proves the relationship between blockchain, smart contracts, partners’ trust, increasing visibility, competitiveness, and environmental performance. In addition, we also proved the vulnerability of smart contracts; our test results fill these gaps. Regarding practical implications, with extended contract periods, partners may expand their doubt in the smart contract and reduce information sharing, further affecting visibility. Manufacturers are reminded that smart contracts may carry hidden trouble that disrupts the relationship between partners’ trust and visibility.First published online 02 March 2022